Profil Motivasi di Pembelajaran Bahasa Kedua (L2): Menjelajahi Interaksi Motivasi Intrinsik dan Ekstrinsik: Studi Kasus di Salah Satu Madrasah Diniyah di Surakarta. - Anita A. Cahyanti; Malikatul Laila; Agus Wijayanto (Samudra Publisher, 2024)
This study investigates and explores the multifaceted interplay between the intrinsic and extrinsic motivations in second language learning (L2) contexts among senior Islamic high school students (MA) learning English as a foreign language in one Islamic Boarding School in Surakarta. Since student achievement is correlated with motivation, it is important in an educational setting. This study employs a qualitative methodology, allowing the researcher to use interviews and observation as two methods of gathering data. Intrinsic motivation among high school students in English language learning and comprehension is the crucial thing although extrinsic motivation has an influence on learning English. Factors influencing intrinsic motivation included are related to their understanding that English is crucial for achieving higher educational goals and their desire to apply English in daily conversations, enjoyment of learning experiences, positive, and supportive classroom environment. Although extrinsic motivation is also essential for students to appreciate their personal growth gaining proficiency in English helps one find an acceptable employment opportunity, importance of good grades in exams, and the Language Task Force (SATGAS BAHASA) also plays a significant role as an extrinsic motivator for both students and the institution in one of Islamic modern boarding school. A balanced interplay between intrinsic and extrinsic motivation is complex but is essential for successful language learning. Extrinsic rewards can initially boost motivation, but intrinsic interest sustains long-term commitment in second language learning.